2012
DOI: 10.1371/journal.pone.0039349
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Mediates the Discriminatory Power of Associative Long-Term Memory in Honeybees

Abstract: Memory is created by several interlinked processes in the brain, some of which require long-term gene regulation. Epigenetic mechanisms are likely candidates for regulating memory-related genes. Among these, DNA methylation is known to be a long lasting genomic mark and may be involved in the establishment of long-term memory. Here we demonstrate that DNA methyltransferases, which induce and maintain DNA methylation, are involved in a particular aspect of associative long-term memory formation in honeybees, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(152 citation statements)
references
References 51 publications
17
135
0
Order By: Relevance
“…Furthermore, stimulus-specific memory changes in a transcription-dependent manner Lefer et al, 2013). These studies are supported by findings that both extinction and stimulus-specific memory are also dependent on transcriptional regulation by DNA methylation (Lockett et al, 2010;Biergans et al, 2012Biergans et al, , 2015.…”
Section: Molecular Mechanisms Of Honey Bee Memory Formationsupporting
confidence: 52%
See 2 more Smart Citations
“…Furthermore, stimulus-specific memory changes in a transcription-dependent manner Lefer et al, 2013). These studies are supported by findings that both extinction and stimulus-specific memory are also dependent on transcriptional regulation by DNA methylation (Lockett et al, 2010;Biergans et al, 2012Biergans et al, , 2015.…”
Section: Molecular Mechanisms Of Honey Bee Memory Formationsupporting
confidence: 52%
“…Furthermore memory performance and transcription and translation dependency varies with factors such as age (Ray and Ferneyhough, 1997;Laloi et al, 2001;Behrends et al, 2007), the exact training protocol (Menzel et al, 2001;Lefer et al, 2013) and satiation levels (Friedrich et al, 2004). Interestingly, 24 hour memory has been repeatedly shown to be dependent on epigenetic -transcription regulating -mechanisms in bees (Lockett et al, 2010;Merschbaecher et al, 2012;Biergans et al, 2012Biergans et al, , 2015 (see: section 1.2.4). This suggests that the question of when a transcription-dependent memory is established in bees is more complex than previously thought.…”
Section: Molecular Mechanisms Of Honey Bee Memory Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, such as honey bees, DNA methyltransferase activity (Wang et al, 2006) is crucial for memory formation (Biergans et al, 2012(Biergans et al, , 2015. DNA methylation also plays a role in the preservation of long term vertebrate memories.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al (2010) showed that rat long term memory (30 days after training) was disrupted by zeb. In invertebrates, such epigenetic mechanisms are also necessary for learning and memory (Lockett et al, 2010;Biergans et al, 2012Biergans et al, , 2015. Thus, DNA methylation is likely an ancestral and conserved mechanism of memory formation.…”
Section: Introductionmentioning
confidence: 99%